EFFECT OF CUT-BACK MC-60 ON PERMEABILITY AND COMPRESSIBILITY OF A GYPSEOUS SOIL - A. Ahmed Al-Sharrad, Muayad (Iraqi Journal of Civil Engineering, 2007)
ABSTRACT A study of the effect of cutback MC-60 on the permeability and compressibility characteristics of sandy gypseous soil is presented. Series of laboratory tests are carried out including classification, compaction, and conventional oedometer tests as well as a new test named compressibility- permeability leaching test. Test results shows that the superlative enhancement in compressibility and permeability and thereby in collapsibility occurred with 7% additive.